2020
DOI: 10.3390/ijerph17155432
|View full text |Cite
|
Sign up to set email alerts
|

Women and Stigma: A Protocol for Understanding Intersections of Experience through Body Mapping

Abstract: This paper outlines a research and dissemination protocol to be undertaken with specific groups of marginalised women in Australia. Women impacted by significant mental distress, disability, or refugee status are among society’s most vulnerable and disenfranchised groups. They can experience significant social exclusion, marginalisation and stigma, associated with reduced help seeking, deprivation of dignity and human rights, and threats to health, well-being and quality of life. Previous research has assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…The connection between what is represented inside the body as a stomach (oval shape, in the center of the trunk, with brownish filling and a colored outline) and the representation of a clock (in the background space of the BMST, connected to the stomach by a greenish trace), which also makes a connection with the mind, is verbally illustrated by the participant: A similar visually represented movement was also found in a study by Larrea-Killinger et al (2020). In everyday life, bodies are dynamic and constantly in motion in response to the environments to which they relate (Boydell et al, 2020;Dennis, 2020;Larrea-killinger et al, 2020). This was represented by Mirror of Mine when describing the relationship between how a bodily sensation, hunger (internal expression), is followed by an external command, which establishes the time for eating as a social norm.…”
Section: Body-map Storytelling: Reflecting On Eating Experiences and ...mentioning
confidence: 60%
See 1 more Smart Citation
“…The connection between what is represented inside the body as a stomach (oval shape, in the center of the trunk, with brownish filling and a colored outline) and the representation of a clock (in the background space of the BMST, connected to the stomach by a greenish trace), which also makes a connection with the mind, is verbally illustrated by the participant: A similar visually represented movement was also found in a study by Larrea-Killinger et al (2020). In everyday life, bodies are dynamic and constantly in motion in response to the environments to which they relate (Boydell et al, 2020;Dennis, 2020;Larrea-killinger et al, 2020). This was represented by Mirror of Mine when describing the relationship between how a bodily sensation, hunger (internal expression), is followed by an external command, which establishes the time for eating as a social norm.…”
Section: Body-map Storytelling: Reflecting On Eating Experiences and ...mentioning
confidence: 60%
“…The applied eating experiences demonstrated how the participants applied the perceptions acquired in the food consciousness intervention to their eating experiences. It was possible to observe an expansion of the repertoire of the relationship between the body and eating behaviors (see Table 2, Considering the PESC's food consciousness intervention experiences, through embodied knowledge (Boydell et al, 2020), the BMST showed sensitivity in communicating the participants' relationship with environmental factors that stimulate food consumption, which influences health and well-being. It was evident that participants were able to experience food practices in different ways (Levitt et al, 2004), integrating the occurrence of insights.…”
Section: Overarching Theme and Thematic Categoriesmentioning
confidence: 99%
“…At the beginning of 2020, we commenced a research project investigating women’s 1 experiences of marginalisation, stigma, and discrimination resulting from their lived experience of disability, mental distress, and/or refugee background ( Boydell et al, 2020 ). We felt an embodied approach to this research was imperative as it would help us understand the lived, and felt, experiences of participants.…”
Section: Background: Covid-19 and The Move To Body Mapping Onlinementioning
confidence: 99%
“…Our research team have experience using body mapping with diverse cohorts (see for example, Dew et al, 2018 ; Malecki et al, 2022 ; Vaughan et al, 2021 ) We originally planned to invite participants to undertake three x two-hour in-person workshop sessions during which they would create a body map that visually represented their experiences of stigma, discrimination, and marginalisation. Workshops were to be followed by a one-on-one interview in which participants discussed their maps and the experiences that informed their creation ( Boydell et al, 2020 ).…”
Section: Background: Covid-19 and The Move To Body Mapping Onlinementioning
confidence: 99%
“…In our own research using body mapping, where participants trace life-size outlines or maps of their bodies and use creative media and words on the map to describe embodied experiences (see Boydell et al, 2020), we did not anticipate any issue with using this participatory method with refugee-background women. However, an advisory committee member who works in the refugee sector pointed out that some participants might feel uncomfortable with the method’s focus on bodies and the familiarity of someone tracing around their bodies due to contextual sociocultural norms.…”
Section: Introductionmentioning
confidence: 99%